PTU-060 The clinical and financial impact of a virtual clinic for biological therapies in inflammatory bowel disease. (22nd June 2015) - Boal, A; Squires, S; Reed, B; Hamid, R; Heydtmann, M; Naismith, G
Abstract : Introduction: Anti-Tumour Necrosis Factor (Anti-TNF) therapy is recognised as an effective treatment for use in Inflammatory Bowel Disease (IBD). Current NICE guidance 1 recommends that disease status should be reassessed every twelve months. This Study aims to assess the impact of a formal IBD team case review by prospectively monitoring clinical and financial outcomes over 12 months. Method: Between April and July 2013, a virtual biological clinic was set up over three dates. Forty-five patients who were receiving Anti-TNF therapy for treatment of IBD at the Royal Alexandra and Vale of Leven hospitals, underwent review. The investigatory group consisted of three consultant gastroenterologists, two IBD clinical nurse specialists and one gastroenterology registrar. Case notes and clinical data via the hospital information system were examined to determine whether investigations were up to date and to identify patients who would benefit from treatment alterations. Data was recorded for significant clinical outcomes for 12 months from the date of implementation of any change to treatment regimen proposed at the virtual clinic. Results: Forty-five patients who were receiving treatment with Anti-TNF therapy (Infliximab n = 34, Adalimumab n = 11) were reviewed. Over the course of twelve months following introduction of the virtual clinic, 14 patients receiving Infliximab therapy and 5 receiving Adalimumab were withdrawn from treatment as they were deemed to have achieved clinical remission. 2 patients had their dosage of Adalimumab reduced from weekly to fortnightly dosing. 1 patient had their treatment and management transferred to their local hospital. 6 patients were switched from Infliximab to Adalimumab as they were thought to be failing therapy. Of the 19 patients withdrawn from therapy, 2 patients had clinical relapse of symptoms during 12 months. These patients were recommenced on treatment, achieving full remission. No patients required steroid therapy or hospital admission due to de-escalation of therapy. The reduction in biological expenditure over 12 months was £236936.34. Cost savings highlight the price of medication only and do not reflect staff time or clinic costs. Conclusion: A virtual biologics clinic ensures that patients on Anti-TNF treatments have disease reassessment and are on appropriate treatment as per clinical guidelines. The interventions appear to have been both safe and cost-effective in this cohort. Disclosure of interest: None Declared. Reference: NICE Guidelines – CE technology appraisals [TA187] Published date: May 2010 Infliximab (review) and Adalimumab for the treatment of Crohn's disease